MESOLITHIC PERIOD OF TRANSCARPATHIA. THE STATE OF THE STUDY - Пеняк, Павло (SWorldJournal, 2025)
The article deals with the results of research of Mesolithic period of Transcarpathia by the well-known Ukrainian archeologist Leonid Matskevy. After the conclusion of scientist, Mesolithic period of edge is presented by two groups of ethno-cultural unity